Abnormal baroreceptor-mediated vasopressin release as possible marker in early diagnosis of multiple system atrophy. Issue 1 (5th January 2004) - Deguchi, K; Sasaki, I; Touge, T; Tsukaguchi, M; Takeuchi, H; Kuriyama, S
Abstract : Background: Although autonomic failure (AF) is a critical symptom of multiple system atrophy (MSA), it may not appear until late in the disease process. Objectives: To clarify whether a detailed investigation of the autonomic nervous system in patients with MSA without overt AF demonstrates latent lesions of central cardiovascular control circuits and facilitates the early diagnosis of MSA. Methods: Autonomic function tests, and plasma noradrenaline (NA) and vasopressin (AVP) responses to head-up tilt (HUT), were studied in 12 patients with MSA with AF (probable MSA), 12 with MSA without overt AF (possible MSA), and 24 controls. Results: Abnormalities of cardiovascular autonomic function tests were prominent in the first group but mild in the second. Plasma NA and AVP increments upon HUT differed significantly among all three groups. Conclusions: These results indicate that probable MSA involves diffuse degeneration of central cardiovascular control circuits. On the other hand, the discrepancies in possible MSA suggest a vulnerability of the noradrenergic (A1) neurones of the caudal ventrolateral medulla that are involved in AVP secretion. This finding also suggests that AVP increment may be useful as a diagnostic tool in the early stages of MSA.